(untitled) (El Hilo de la Fabula, 2020)
The article considers American works of fiction produced in the 21st Century from a philosophical approach, specifically around the concept of «linguistic turn». Centered on the problematic of justice, and inspired by the ideas developed by Jürgen Habermas (1929–) and Richard Rorty (1931–2007), its hypothesis centers on the idea that justice results from a dialogical construction that accounts for the pluralism inherent to the interpretation of the world. It complements this initial point of view by resorting to the notion of Chantal Mouffe’s «agonistic pluralism».